Problem Based Learning Assisted by Google Classroom on Conceptual Understanding Ability - Prihatini, Fajar; Utami, Wikan Budi; Aulia, Fikri; Fadila, Fariz (Jurnal Bahasa Inggris, 2021)
The purpose of the present study is to determine the effectiveness of the problem-based learning model that assisted Google Classroom in the ability of conceptual understanding. This study adapted experimental research with a post-test-only control design. The population of the study is the students of the English Education study program in the first semester consisting of two classes. The sample used in this study was Class 1B with problem-based learning assisted Google Classroom with question menu and Class 1A using problem-based learning assisted Google Classroom with assignment menu. Test and documentation are used for collecting the data in conducting this study. The technique of analyzing the data used an independent sample t-Test and N-Gain test. The result showed that the students who were taught using problem-based learning assisted Google Classroom model with questions menu had better conceptual understanding skills than the students who were taught problem-based learning assisted Google Classroom with assignment menu.